Uso das boas práticas obstétricas na atenção ao parto seguro: um estudo de validação - Vieira, Maraysa Jéssyca de Oliveira (2020)
Introduction: Public policies in the field of maternal and child health have pointed to the importance of humanizing health care through the adoption of practices based on scientific evidence that respect women's rights, individuality, integrality and autonomy in different scenarios of attention. Objective: To validate the content of an instrument that analyzes the use of good obstetric practices by health professionals in the care of safe delivery. Methodology: This is a methodological research, with a quantitative approach, based on the validation of an instrument based on the first six steps of the Content Validation Technique according to Pasquali. The participants were doctors and nurses who work in obstetric care in Brazilian states. The data were collected using a structured instrument with data identifying the participants, in addition to the instrument being validated. The data of the participants were analyzed in a descriptive way, whereas those referring to the analysis of the content of the instrument, were evaluated quantitatively through the Content Validation Index (CVI). Results: Ten judges participated in the survey, five doctors and five nurses. All of them have a specialization in obstetrics, with a time in the area that varies from two to 30 years, with an average of 12.2 years. Regarding content validation, of the 23 items proposed in the instrument, 20 items (including the title) obtained CVI 80% to 100%, and four CVI 60% to 70%. Items that obtained rates lower than 80% were disregarded, ending the instrument with 19 items. Conclusion: The instrument was validated for its content, with more than 80% of the items proposed in the instrument being considered representative by the judges to assess the use of good obstetric practices by health professionals in the care of safe delivery.